Characteristics of Viral Shedding Time in SARS-CoV-2 Infections: A Systematic Review and Meta-Analysis - Yan, Danying; Zhang, Xiaobao; Chen, Can; Jiang, Daixi; Liu, Xiaoxiao; Zhou, Yuqing; Huang, Chenyang; Zhou, Yiyi; Guan, Zhou; Ding, Cheng; Chen, Lu; Lan, Lei; et al. (Frontiers in Public Health, 2021)
Background: The viral shedding time (VST) of SARS-CoV-2 mainly determines its transmission and duration of infectiousness. However, it was heterogeneous in the existing studies. Here, we performed a meta-analysis to comprehensively summarize the VST of SARS-CoV-2. Methods: We searched PubMed, Web of Science, MedRxiv, BioRxiv, CNKI, CSTJ and Wanfang up to October 25, 2020, for studies that reported VSTs of SARS-CoV-2. Pooled estimates and 95% CIs for the VSTs were calculated using log-transformed data. The VSTs in SARS-CoV-2 infections based on different demographic and clinical characteristics, treatments and specimens were stratified by subgroup analysis. Results: A total of 35 studies involving 3385 participants met the inclusion criteria. The pooled mean VST was 16.8 days (95% CI: 14.8-19.4, I2 = 99.56%) in SARS-CoV-2 infections. The VST was significantly longer in symptomatic infections (19.7 days, 95% CI: 17.2-22.7, I2 = 99.34%) than in asymptomatic infections (10.9 days, 95% CI: 8.3-14.3, I2 = 98.89%) (P < 0.05). The VST was 23.2 days (95% CI: 19.0-28.4, I2 = 99.24%) in adults, which was significantly longer than that in children (9.9 days, 95% CI: 8.1-12.2, I2 = 85.74%) (P < 0.05). The VST was significantly longer in persons with chronic diseases (24.2 days, 95% CI: 19.2-30.2, I2 = 84.07%) than in those without chronic diseases (11.5 days, 95% CI: 5.3-25.0, I2 = 82.11%) (P < 0.05). Persons receiving corticosteroid treatment (28.3 days, 95% CI: 25.6-31.2, I2 = 0.00%) had a longer VST than those without corticosteroid treatment (16.2 days, 95% CI: 11.5-22.5, I2 = 92.27%) (P = 0.06). The VST was significantly longer in stool specimens (30.3 days, 95% CI: 23.1-39.2, I2 = 92.09%) than in respiratory tract specimens (17.5 days, 95% CI: 14.9-20.6, I2 = 99.67%) (P < 0.05). Conclusions: A longer VST was found in symptomatic infections, infected adults, persons with chronic diseases, and stool specimens.